2438. Ceftolozane/Tazobactam (C/T) Against Multidrug-Resistant Pseudomonas aeruginosa (MDR-Pa) Infections: Clinical Efficacy, and Baseline and Emergent Resistance. (26th November 2018) - Shields, Ryan K; Haidar, Ghady; Potoski, Brian A; Doi, Yohei; Marini, Rachel V; Nguyen, M Hong; Clancy, Cornelius J
Abstract: Background: Experience is mounting for C/T against MDR-Pa infections. More data are needed on efficacy for different infections, and baseline and emergent resistance. Methods: We retrospectively reviewed patients receiving >48 hours of C/T for MDR-Pa infections. Clinical success was defined at 30 days as survival, improved symptoms, and absence of recurrent infection. Microbiologic failures were defined as isolation of MDR-Pa following ≥7 days of C/T. Minimum inhibitory concentrations (MICs) were determined by broth microdilution. Results: 63 patients were included. Median age was 58 (range: 23–91), 54% were men, and median Charlson score was 4 (0–12). 35% were transplant recipients. At onset of infection, median APACHE II and SOFA scores were 21 (2–49) and 5 (0–17), respectively. Infections included pneumonia ( n = 45), tracheobronchitis ( n = 4), intra-abdominal ( n = 4), skin/soft tissue ( n = 3), urinary tract ( n = 3), bacteremia ( n = 2), endocarditis and empyema ( n = 1 each). Median duration of C/T was 13 days (3–52). 58% of patients with pneumonia received concomitant inhaled antibiotics. 30% patients received concomitant intravenous antibiotics. Overall rates of clinical success and survival at 30 days were 57% and 78%, respectively. Failures were due to death ( n = 14), recurrent infection ( n = 7), lack of clinical improvement ( n = 5), or early discontinuation of C/T ( n = 1). Rates of success and survival for pneumonia were 53% and 71%, respectively. Success rates were 67% and 51% among patients receiving C/T mono- vs. combination therapy ( P = 0.29). Among surviving patients ( n = 49), microbiologic failures occurred in 49% at a median of 23 days (7–64) from C/T initiation. Micro failures were due to recurrent pneumonia ( n = 6) or colonization ( n = 18). 56% of patients survived at 90 days. Median C/T MIC vs. baseline MDR-Pa isolates was 2 µg/mL (range: 0.5–>256); 10% of patients had C/T resistant isolates at baseline. Among patients with microbiologic failures infected by C/T susceptible isolates at baseline ( n = 21), 38% developed resistance. The median duration of treatment prior to the emergence of resistance was 17 days (6–53). Conclusion: C/T was effective for treatment of various MDR-Pa infections. MDR-Pa cannot be assumed to be C/T susceptible at baseline, and MICs should be measured before treatment and following microbiologic failure. Disclosures: R. K. Shields, Allergan: Grant Investigator, Research grant. Pfizer: Consultant and Scientific Advisor, Speaker honorarium. Shionogi: Scientific Advisor, Consulting fee. Roche: Grant Investigator, Research grant. Venatorx: Grant Investigator, Research grant. Medicines Company: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Accelerate Diagnostics: Scientific Advisor, Consulting fee. M. H. Nguyen, Merck: Grant Investigator, Research grant. Astellas: Grant Investigator, Research grant.